A moda e o sagrado: a interferência da doutrina na estética feminina - Oliveira, Thaís Regina da Silva (2014)
Fashion possesses, as a field of action, studies that permeate symbologies which delimit identities of social groups. Along these lines, this thesis intends to comprehend the existing relation between religiosity and fashion, since the religious aspect may be intimately entailed to the conduct of certain social groups, as the evangelical, for instance. Thus, this group becomes an important market niche to be taken in consideration by fashion professionals, who should develop products that ally fashion and doctrine. This relation is grounded in studies that pervade consumption culture and identity construction, considering, in this case, doctrines disseminated by evangelical traditional religions. The present project is based on bibliographic research, exploring and merging the concepts of fashion and religiosity. The methodology to be employed will be centered in qualitative research which presents itself as a tool to achieve the pre-determined objectives. Therefore, semistructured polls will be applied to female gender young people who are part of the group in question, as many as necessary, until the answers achieve regularity. As a result of this research, it will be created a fashion brand that combines religious, esthetic and social precepts, reinforcing the identity of this social group with the possibility of being in fashion.